Hourglass‐like constrictions on MRI are common in electromyography‐confirmed cases of neuralgic amyotrophy (Parsonage–Turner syndrome): A tertiary referral center experience - Sneag, Darryl B.; Urban, Casey; Li, Tim Y.; Colucci, Philip G.; Pedrick, Emily G.; Nimura, Clare A.; Feinberg, Joseph H.; Milani, Carlo J.; Tan, Ek T. (Muscle & nerve, 2024)
Introduction/Aims Hourglass‐like constrictions (HGCs) of involved nerves in neuralgic amyotrophy (NA) (Parsonage–Turner syndrome) have been increasingly recognized with magnetic resonance neurography (MRN). This study sought to determine the sensitivity of HGCs, detected by MRN, among electromyography (EMG)‐confirmed NA cases. Methods This study retrospectively reviewed records of patients with the clinical diagnosis of NA, and with EMG confirmation, who underwent 3‐Tesla MRN within 90 days of EMG at a single tertiary referral center between 2011 and 2021. “Severe NA” positive cases were defined by a clinical diagnosis and specific EMG criteria: fibrillation potentials or positive sharp waves, along with motor unit recruitment (MUR) grades of “discrete” or “none.” On MRN, one or more HGCs, defined as focally decreased nerve caliber or diffusely beaded appearance, was considered “imaging‐positive.” Post hoc inter‐rater reliability for HGCs was measured by comparing the original MRN report against subsequent blinded interpretation by a second radiologist. Results A total of 123 NA patients with 3‐Tesla MRN performed within 90 days of EMG were identified. HGCs were observed in 90.2% of all NA patients. In “severe NA” cases, based on the above EMG criteria, HGC detection resulted in a sensitivity of 91.9%. Nerve‐by‐nerve analysis (183 nerve‐muscle pairs, nerves assessed by MRN, muscles assessed by EMG) showed a sensitivity of 91.0%. The second radiologist largely agreed with the original HGC evaluation, (94.3% by subjects, 91.8% by nerves), with no significant difference between evaluations (subjects: χ2 = 2.27, P = .132, nerves: χ2 = 0.98, P = .323). Discussion MRN detection of HGCs is common in NA.